The Problematics of Unclaimed Royalty Funds in The Governance of National Collective Management Organizations in Indonesia - Maria Magdalena Astrina Bratajaya; Azis Budianto (Ridwan Institute, 2026)
The management of music royalties is part of the protection of creators’ economic rights, as stipulated in Law No. 28 of 2014 on Copyright, specifically Articles 87 to 93 concerning royalty management through Collective Management Organizations. To improve the effectiveness of royalty collection and distribution, the government established a one-stop management system through the National Collective Management Organization (LMKN), as regulated in Government Regulation No. 56 of 2021. However, in practice, the issue of unclaimed royalty funds persists due to unregistered creators, limited data on the use of works, and the suboptimal integration of the royalty distribution system. This study aims to analyze the legal framework governing music royalty management and the status of unclaimed royalty funds within the National Collective Management Organization system, as well as to examine issues related to the management and distribution of unclaimed royalty funds in the practical governance of the LMKN. The research method used is normative legal research, employing statutory and analytical approaches. The results of the study indicate that the royalty management system is centrally regulated through the LMKN and distributed periodically through Collective Management Organizations (LMKs) to creators based on data regarding the use of works. However, unclaimed royalty funds remain due to data limitations and the fact that some creators have not yet registered with a Collective Management Organization. These funds are temporarily held by the LMKN until the rights holders file a claim. This situation creates uncertainty regarding the fulfillment of creators’ economic rights, thereby necessitating improved data collection, greater transparency in governance, and stronger integration among stakeholders involved in music royalty management.